2022
DOI: 10.15212/amm-2022-0025
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in cancer therapy based on the combination of ferroptosis with photodynamic therapy

Abstract: Current anticancer treatments have many limitations to achieving high efficacy. Hence, novel strategies that broaden therapeutic prospects must urgently be developed. Ferroptosis is an iron-dependent form of non-apoptotic programmed cell death that is induced by cellular antioxidative system inhibition. Photodynamic therapy (PDT) uses photosensitizers to generate reactive oxygen species and aggravate oxidative stress in tumor cells. Combining ferroptosis with PDT cooperatively regulates intracellular redox hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 116 publications
(143 reference statements)
0
9
0
Order By: Relevance
“…ROS production is a common pathway for ferroptosis therapy, sonodynamic therapy (SDT), and photodynamic therapy (PDT). [80,81] TCPP, a member of the porphyrin family of macromolecular heterocyclic compounds, is capable of generating ROS upon light/acoustic stimulation. [72,82] Importantly, TCPP can be liganded with metal ions to form MOF without additional modification.…”
Section: Tcpp-bearing Mofsmentioning
confidence: 99%
“…ROS production is a common pathway for ferroptosis therapy, sonodynamic therapy (SDT), and photodynamic therapy (PDT). [80,81] TCPP, a member of the porphyrin family of macromolecular heterocyclic compounds, is capable of generating ROS upon light/acoustic stimulation. [72,82] Importantly, TCPP can be liganded with metal ions to form MOF without additional modification.…”
Section: Tcpp-bearing Mofsmentioning
confidence: 99%
“…41 Also, when using nMOFs as a carrier in vivo , they can be captured by immune cells such as Macrophage; in order to maximize the therapeutic effect, it is also highly desirable to realize their abilities to target specific tumors and evade immune clearance. 121,122 Much effort has been devoted to decreasing immune clearance through the conjugation of specific targeting moieties on the MOF's surface, such as folate, antibodies, and peptides, but complex preparations have frequently restricted such approaches, which still needs to be deeply explored.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…PDT also promotes ferroptosis by non-enzymatic lipid peroxidation and sensitizes the tumor cells to ferroptosis via immunological effects. [33][34][35][36] For instance, Yu et al reported an acidity activated micelle for PPa-involved PDT, and the recruited tumor-infiltrating T lymphocytes further benefited the treatment of cancer cells with RSL3-inducible ferroptosis to inhibit the growth of melanoma and metastatic breast tumors. 12 Hao et al tailored HEK293T cell-secreted exosomes that overexpressed CD47 to escape recognition by the mononuclear phagocyte system and induce ferroptosis following 532 nm laser-excited PDT.…”
Section: Introductionmentioning
confidence: 99%